Population pharmacokinetics and dose optimization of ceftazidime in critically ill children - Li, Mengting; Gao, Liuliu; Wang, Zuo; Zeng, Lingkong; Chen, Chen; Wang, Jun; Li, Sichan; Liu, Maochang; Wang, Yang (Frontiers in Pharmacology, 2024)
The aim of this study was to develop a population pharmacokinetics model for ceftazidime in critically ill children in the pediatric ICU (PICU) and to optimize an appropriate dosing regimen for this population. Methods: We performed a prospective pharmacokinetics research on critically ill children aged 0.03 to 15 years. The population pharmacokinetics model was developed with the NLME program. Statistical and graphical methods were used to assess the stability and predictive performance of the model. Monte Carlo simulations were conducted to determine the optimal ceftazidime dosing regimen to achieve 70% fT > MIC.Results: This study included 88 critically ill children and 100 ceftazidime serum concentrations. The pharmacokinetics characteristics of ceftazidime were best described by a one-compartment linear elimination model. Weight and estimated glomerular filtration rates (eGFR) were determinant covariates for clearance (CL) of ceftazidime. The recommended ceftazidime dosage regimens attained a probability of target attainment (PTA) > 90% for critically ill children at minimum inhibitory concentration (MIC) values of 2, 4, and 8 mg/L. For bacterial infection at an MIC of 16 mg/L, the commonly used dose of ceftazidime is difficult to achieve effective pharmacodynamics (PD) targets in vivo.The population pharmacokinetics model of ceftazidime were established in critically ill children. Based on this model, we recommend evidence-based, individualized dosing regimens for subgroups with different weights and renal functions. The current daily dosage for children adequately meets treatment requirements for MICs of 2, 4, and 8 mg/L, while for bacterial infection at an MIC of 16 mg/L, an elevated dosage regimen may be required.